Global Energy Transitions, Prospects and Projections for 2030 - Elene Pantskhava; Maka Jishkariani (Research Retrieval and Academic Letters, 2025)
The combination of growing momentum behind clean energy technologies and structural economic changes around the world is having a significant impact on fossil fuels, coal, oil, and natural gas. The transition to clean energy to meet global demand is underway around the world, it is an unstoppable process, and the sooner it happens, the better for all of us. Governments, companies and investors should protect clean energy transitions rather than hinder them. There are huge benefits on offer, including new industrial opportunities and jobs, greater energy security, cleaner air, universal energy access and a safer climate for all. Accordingly, the existing electricity infrastructure must be expanded and modernized to create a new energy system for renewable energy sources. Given the ongoing tensions and volatility in traditional energy markets today, claims that oil and gas represent a safe or secure choice for the world’s energy and climate future are weaker than ever. Worsening climate impacts are undermining the security of the energy system. If countries deliver on their national energy and climate pledges on time and in full, progress on clean energy will accelerate. However, even stronger measures will be needed to keep global warming to 1.5°C. The paper presents world energy forecasts for the near and medium term, emphasis is placed on climate change goals and economic development